Funkcje form komicznych (memów internetowych i dowcipów) związanych z pandemią COVID-19 - Szagun, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The subject of the study is the analysis of a series of Internet memes and linguistic jokes made available in pseudomemic form in connection with the COVID-19 pandemic. Comedy itself feeds on any deviations from the norm observed in social, and especially political, life; it captures all the aberrations, nonsense and inconsistencies. The pandemic emergency is fraught with new situations and rules that constitute such a deviation. A vivid social reaction is especially visible in the multisemiotic comic genres, such as Internet memes, due to their channel of entry (the Internet becomes the main channel of communication outside of family communities during social isolation), plasticity and susceptibility to replication. Comic forms, apart from peculiarly ludic and humorous functions, also perform persuasive functions, activating the social need to differentiate between oneself and the stranger, and consequently isolate or integrate certain social groups. In addition, Internet memes also serve as a commentary on current events, thus prompting the audience to take a position. Persuasion dressed in a comic costume seems to be one of the strongest ways of social influence, because it spreads in its innocent and playful form like a viral and becomes firmly fixed in social consciousness.